2021
DOI: 10.1002/ejic.202100039
|View full text |Cite
|
Sign up to set email alerts
|

ONO‐Pincer‐Type Coumarin‐Based Copper(II) Metalates: Effect on Alzheimer's Disease Pathologies in Caenorhabditis elegans

Abstract: Four copper(II) complexes 1-4 of 3-acetylchromene-2-one and substituted 3-acetylchromene-2-one derived Schiff bases were synthesized and structurally characterized using analytical and spectral techniques. The molecular structure of complex 1 has been confirmed by single crystal X-ray diffraction studies, which revealed that ligand 3-acetylchromene-2-one-4 N-semicarbazone is coordinated to the metal as ONO pincer type ligand. Two nitrate molecules are coordinated to the copper ion through oxygen atoms, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In the AOX‐Fe 2+ system, multiplet (appeared as broad) observed at δ 7.35–7.64 ppm indicated the presence of coumarin ring protons of the probe. In the AOX‐Fe 2+ IR spectrum (Figure S13), the C=O and C=N groups stretching frequency of AOX decreased from 1759 cm −1 to 1668 cm −1 and 1600 cm −1 to 1561 cm −1 respectively [42] . The obtained results suggested the coordination of oxygen and nitrogen atoms to the Fe 2+ ion.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In the AOX‐Fe 2+ system, multiplet (appeared as broad) observed at δ 7.35–7.64 ppm indicated the presence of coumarin ring protons of the probe. In the AOX‐Fe 2+ IR spectrum (Figure S13), the C=O and C=N groups stretching frequency of AOX decreased from 1759 cm −1 to 1668 cm −1 and 1600 cm −1 to 1561 cm −1 respectively [42] . The obtained results suggested the coordination of oxygen and nitrogen atoms to the Fe 2+ ion.…”
Section: Resultsmentioning
confidence: 76%
“…In the AOX-Fe 2 + IR spectrum (Figure S13), the C=O and C=N groups stretching frequency of AOX decreased from 1759 cm À 1 to 1668 cm À 1 and 1600 cm À 1 to 1561 cm À 1 respectively. [42] The obtained results suggested the coordination of oxygen and nitrogen atoms to the Fe 2 + ion. Based on literature, it was found that the iron complexes undergo coordination with Schiff bases resulting in the formation of stable five or six coordinated complexes.…”
Section: Job's Plotmentioning
confidence: 79%
“…The band appeared at 1542 and 1527 cm −1 corresponding to ν (CN) in the ligands AFIZ and BFIZ respectively was shifted to 1511 and 1521 cm −1 in the complexes PRAFIZ and PRBFIZ indicating the coordination of azomethine nitrogen to ruthenium ions. 39 In the ligands, the bands at 1648 and 1671 cm −1 corresponding to the presence of ν (CO) disappeared in the complexes and a new band appeared at 1371 and 1373 cm −1 corresponding to ν (C–O) indicating the coordination of the ligands through the enolic oxygen atom of the ligands to ruthenium ions (Table S1†). 40,41 Electronic spectra of the ligands ( AFIZ , BFIZ ) and their corresponding Ru( ii ) complexes ( PRAFIZ , PRBFIZ ) were recorded in methanol (10 μM) in the range of 200–800 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic absorption band due to nitrate was also observed for the complexes ( Co1 ‐ Co4 ) at 1382–1384 cm −1. [ [ 29 ] ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 25,28 ] A bands appeared around 3043–3066 and 1669–1714 cm −1 due to the vibration of the –NH and C=O group of semicarbazone moiety present in the ligands, HL 1 and HL 3 these bands disappeared completely in the complexes Co1 and Co3 , and a new band appeared at 1294–1309 cm −1 corresponding to a possible νC − O vibration, indicating the coordination of oxygen atom after enolization followed by deprotonation. [ 29 ] The bands appeared around 3141–3239 cm −1 and 833–840 cm‐1 due to the vibration of the –NH and C=S group present in the ligands HL 2 and HL 4 which disappeared in the spectra of the complexes Co2 and Co4 and a new band for C‐S appeared at 703–707 cm −1 indicating that the coordination is through the thiolate sulfur after enolisation followed by deprotonation on sulfur. [ 30–33 ] In the complexes Co1 and Co3 the band appeared at 3355–3357 cm −1 due to the vibration of the ‐OH group of water moiety.…”
Section: Resultsmentioning
confidence: 99%